Evaluating the influence of sleep quality and quantity on glycemic control in adults with type 1 diabetes - Botella-Serrano, Marta; Velasco, Jose Manuel; Sánchez-Sánchez, Almudena; Garnica, Oscar; Hidalgo, J. Ignacio (Frontiers in Endocrinology, 2023)
Background: Sleep quality disturbances are frequent in adults with type 1 diabetes. However, the possible influence of sleep problems on glycemic variability has not been deeply studied in the past. This study aims to assess the impact of sleep quality and sleep quantity on glycemic control. Materials and Methods: Observational study in 25 adults with type 1 diabetes, simultaneous recording of continuous glucose monitoring (Abbott FreeStyle Libre system) for 14 days, and a sleep study by wrist actigraphy (Fitbit Ionic device). The study analyzes, using artificial intelligence techniques, the relationship between the quality and structure of sleep with time in normo-, hypo-, and hyperglycemia ranges and with glycemic variability. The patients are also studied as a group, comparing patients with good and poor sleep quality. Several cluster analyses and correlational studies are performed Results: A total of 243 days/nights were analyzed, of which 77% (n=189) were categorized as poor quality and 33% (n=54) as good quality. Linear regression methods find a correlation (r=0.8) between the variability of sleep efficiency and the variability of mean blood glucose. With clustering techniques, patients were grouped according to their sleep structure (characterizing this structure from the number of transitions between the different sleep phases). These clusters show a relationship between time in range and sleep structure. Conclusions: This study suggests that poor sleep quality is associated with lower time in range and greater glycemic variability, so improving sleep quality in patients with type 1 diabetes could improve their glycemic control.